2021
DOI: 10.3390/nu13020361
|View full text |Cite
|
Sign up to set email alerts
|

The Immunopathogenesis of Alzheimer’s Disease Is Related to the Composition of Gut Microbiota

Abstract: The microbiota–gut–brain axis plays an important role in the development of neurodegenerative diseases. Commensal and pathogenic enteric bacteria can influence brain and immune system function by the production of lipopolysaccharides and amyloid. Dysbiosis of the intestinal microbiome induces local and consecutively systemic immune-mediated inflammation. Proinflammatory cytokines then trigger neuroinflammation and finally neurodegeneration. Immune-mediated oxidative stress can lead to a deficiency of vitamins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 322 publications
(238 reference statements)
0
56
0
2
Order By: Relevance
“…Both experimental and clinical studies found that the decrease of gut microbiota diversity was common in AD animal models and patients. In addition, the structure of gut microbiota has also changed [ 51 ]. In the animal model of intestinal malnutrition caused by ampicillin for one month, it was found that the spatial learning and memory ability of experimental animals was damaged and aggressive behaviors increased [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and clinical studies found that the decrease of gut microbiota diversity was common in AD animal models and patients. In addition, the structure of gut microbiota has also changed [ 51 ]. In the animal model of intestinal malnutrition caused by ampicillin for one month, it was found that the spatial learning and memory ability of experimental animals was damaged and aggressive behaviors increased [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation of intracellular neurofibrillary tangles, due to hyperphosphorylation of tau proteins 6,7 ; 4. Oxidative stress 8,9 ; 5. Chronic peripheral 8,10 and neuro-inflammation 11 by microglial activation; 6.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic changes associated with inflammatory processes and monoaminergic neurotransmitters play a role in disease 43 and psychological disorders, such as anxiety or depression 44 47 . Lactobacillus reuteri intake improved depressive-like behaviour in mice by reversing the stress-induced decrease of fecal H 2 O 2 levels and depleting the resident Lactobacillus population 35 .…”
Section: Introductionmentioning
confidence: 99%